A methodology to approach immigrants' land use in metropolitan areas - Emília Malcata Rebelo (2010)
This paper proposes a methodological approach to regional and urban planning in order to design, settle and manage a public policy for the attraction, location and distribution of different groups of immigrants. It further develops a set of decision-support tools, including a management information system and an integrated and interactive model in order to: (i) characterize the patterns of residential land used by different groups of immigrants according to their professional features, and respective evolution, (ii) anticipate the location of new immigrants or groups of immigrants that arrive into the studied territory (according to their demographic, economic and professional characteristics, keeping or changing the prevailing socio-economic, planning and territorial structure), and respective evolution, and (iii) monitor the evolution of respective social, economic and professional territorial integration. This methodology and set of tools are applied, as a case study, to the Oporto Metropolitan Area (Portugal). They possess display and simulation functionalities that support the test and implementation of local, regional and urban policy strategic decisions. Once workmanship quantitative and qualitative needs are specified - according to regional overall prevailing strategies - it outlines the socio-economic-professional conditions to welcome and to fulfil the needs of different population groups - through provision of proper housing, infrastructures, equipments and jobs, as well as through governance mechanisms - in the scope of socio-economic sustainability and life quality principles.